Amidoselenation of Alkenes Yielding the β-Amido-selenides through a Radical Pathway - Zhao, Feng; Sun, Ting; Liu, Zhenhua; Sun, Kai; Zhang, Chong; Wang, Xin (Current Organic Chemistry, 2018)
An efficient protocol for the intermolecular amidoselenation of alkenes with diphenyl diselenides and acetonitrile has been developed that affords a series of β-amidoselenides in high yields under mild conditions. The preliminary experimental results support the involvement of active benzyl radical species, and a radical pathway was therefore proposed for the reaction.
Keywords: transformation